2001
DOI: 10.1034/j.1600-0773.2001.d01-157.x
|View full text |Cite
|
Sign up to set email alerts
|

Spasmolytic Effects of Three Harmala Alkaloids onGuinea-Pig Isolated Trachea

Abstract: The present study examined and compared the spasmolytic effects of 3 harmala alkaloids, harmine, harman, and harmaline, on carbachol-, histamine-, and KCl-induced contractions of guinea-pig isolated tracheal preparations. All 3 compounds relaxed the tracheal preparations contracted by these spasmogens with similar or different EC50 values, harmine being the most potent one. The cumulative concentration-response curves of all 3 compounds for carbachol-induced contraction were shifted to the right by propranolol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…This is partially supported by the findings of Shi et al . (2000; 2001), who used binding receptor assays to demonstrate an interaction of the related compound harmine with the 1,4‐dihydropyridine‐binding site of L‐type calcium channels of cardiac cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is partially supported by the findings of Shi et al . (2000; 2001), who used binding receptor assays to demonstrate an interaction of the related compound harmine with the 1,4‐dihydropyridine‐binding site of L‐type calcium channels of cardiac cells.…”
Section: Discussionmentioning
confidence: 99%
“…It appears surprising that, despite these manifold effects of harmale alkaloids on various targets, little information is available about their action on neuronal sodium, potassium and calcium channel currents and calcium homeostasis (Shi et al ., 2001). Especially calcium – entering through membrane channels – acts as a major second messenger, whose intracellular concentration is tightly regulated.…”
Section: Introductionmentioning
confidence: 99%
“…1). These harmala alkaloids have a wide spectrum of pharmacological action including platelet aggregation inhibition [2], monoamine oxidase inhibition [3,4], anxiolytic and behavioral effects [3], spasmolytic effects [5], and immunomodulatory effects [6]. Thus, it is important to develop an efficient method to separate and purify alkaloids from the plants.…”
Section: Introductionmentioning
confidence: 99%
“…These alkaloids are considered to possess pharmacological properties related to the central nervous system -tremorogenesis (12), hypothermia (1), hallucinogenesis (8) and monoamine oxidase inhibition (13,15). In experimental animals (guinea-pigs), harmane, harmine and harmaline have also been demonstrated to cause spasmolytic effects on isolated trachea (17). It has also been reported that harmane alkaloids show antioxidant and radical scavenging properties (9,20), cause inhibition of platelet aggregation (16), exert cytotoxic effects on cancer cell lines (16), and possess anthelmintic and antiprotozoal activities (2).…”
Section: Introductionmentioning
confidence: 99%